NUMERICAL AND EXPERIMENTAL ANALYSIS OF THE FLOW OVER A COMMERCIAL VEHICLE - PICKUP - Pinto, W. J. G. S.; Almeida, O. (Revista de Engenharia Térmica, 2018)
This work presents an ongoing numerical and experimental study of the flow around a pickup vehicle by means of CFD simulations and wind tunnel experiments. The model was based on the light-pickup market in Brazil and it was designed with flat surfaces and sharp edges. One of the objectives of this research was the understanding about the flow pattern around the vehicle, especially in the region behind the cabin and the wake. Another goal was to obtain original data from experimental measurements which could be used on further computational investigations. The experiments were carried out in a low-speed wind tunnel at Reynolds number of 5 x 105. Hot-wire anemometry was used to obtain the velocity profiles. Wall tufts were applied to describe the flow direction and regions of attached/detached and recirculation zones. Acceleration due to the underbody and the shear layer formed on the cabin were well defined, also indicating a region of reverse flow behind the tailgate. The flow visualization allowed the identification of recirculation regions inside the trunk and regions of detached flow. These flow patterns were also reproduced in the CFD simulations resulting satisfactory information to describe the main flow pattern over the pickup vehicle.